PERCEPTIONS OF SOCIAL MEDIA–INFORMED MANAGEMENT STRATEGIES IN HIGHER EDUCATION: EVIDENCE FROM YUNNAN UNIVERSITY OF FINANCE AND ECONOMICS - Qifei Chen; Nedpogaeo , Asawin (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This study investigates how social media big data, viewed from a psycho-social perspective, influences higher education management strategies, using Yunnan University of Finance and Economics as the case context. A quantitative, cross-sectional survey design was adopted. Two self-administered questionnaires (originally developed in Chinese) were used for faculty and students, with 5-point Likert items and reverse-scored items where applicable. Stratified sampling and data screening yielded 330 valid faculty and 420 valid student responses. Reliability and construct validity were assessed using SPSS 26.0. Hierarchical regression tested direct effects and a mediation pathway in which Impact on Work and Life (IWL) mediates links between key predictors and Higher Education Management Strategies (HEMS). Bootstrap mediation was used for indirect effects. After adding predictors, the model explained substantial variance in HEMS. Usage awareness, knowledge and skills, and organizational support/environment significantly and positively predicted HEMS. Predictors also explained IWL, and IWL strongly predicted HEMS. Bootstrap results confirmed significant indirect effects for all three predictors , indicating partial mediation. The study links psycho-social readiness and organizational conditions to data-informed higher education management outcomes and clarifies the mediating role of work–life impacts in this process.